STUDI EKSPLORASI BIAS ORIENTATION DAN COGNITIVE KNOWLEDGE DALAM SUKSESI USAHA RM. SIMPANG RAYA PADANG - Aufa Rahmatika; Hafiz Rahman (Research Center and Case Clearing House PPM School of Management, 2020)
The variety of businesses that exist, including family businesses, makes these businesses have to determine strategies to be able to survive. Among the strategies that must be done is to strive for succession to run from the first generation to the next generation. Business succession is carried out aiming to reorganize business governance so as to achieve a balanced state. The purpose of this study was to analyze the orientation and cognitive knowledge of founders and successors in managing business succession at Simpang Restaurant. This study uses descriptive qualitative methods with data analysis data processing techniques. The results show that the succession that was carried out initially went well, but in recent years there have been obstacles related to differences in orientation and cognitive knowledge between current founders and successors. The difference in purpose and knowledge orientation about the restaurant business between the two managers is very different. So that the current successor is uncertain and needs to learn many things related to the ins and outs and internal and external management of the restaurant.